2015
DOI: 10.1007/978-3-319-24223-1_8
|View full text |Cite
|
Sign up to set email alerts
|

KRAS-Mutant Lung Cancers in the Era of Targeted Therapy

Abstract: KRAS-mutant lung cancers account for approximately 25% of non-small cell lung carcinomas, thus representing an enormous burden of cancer worldwide. KRAS mutations are clear drivers of tumor growth and are characterized by a complex biology involving the interaction between mutant KRAS, various growth factor pathways, and tumor suppressor genes. While KRAS mutations are classically associated with a significant smoking history, they are also identified in a substantial proportion of never-smokers. These mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…Despite intense efforts to target KRAS or its key effectors, compensatory pathways have limited the ability of such agents to achieve clinical impact [26, 27]. Although KRAS drives tumorigenesis of lung and pancreatic cancer, we and others [3] find that only certain KRAS mutant lung cancers continue to need KRAS during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite intense efforts to target KRAS or its key effectors, compensatory pathways have limited the ability of such agents to achieve clinical impact [26, 27]. Although KRAS drives tumorigenesis of lung and pancreatic cancer, we and others [3] find that only certain KRAS mutant lung cancers continue to need KRAS during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors bind to their receptors, receptor auto-phosphorylation occurs leading to activation of downstream signaling cascades such as the phosphoinositide-3-kinase (PI3K)/Protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway that results in increased survival/proliferation and inhibition of apoptosis [10,11,12,13]. Another pathway activated by GF signaling is the RAS/mitogen activated protein kinases (MAPK) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Another pathway activated by GF signaling is the RAS/mitogen activated protein kinases (MAPK) pathway. GF binding to the activated receptor through the involvement of the Grb2/SOS complex renders Ras in the GTP-bound form, activating Raf, MEK and MAPK further downstream [13,14,15,16]. Cancer cells often exhibit mutations that allow them to constitutively enhance proliferation while inhibiting apoptosis/cell death pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that small RhoGTPase play an important role in small cell lung cancer (Bhattacharya et al, 2015;Naidoo and Drilon, 2016). Therefore, possible use of statins or prenylation inhibitors in combination with standard therapy of non-small cell lung cancer may improve the clinical outcome of this incurable and devastating disease.…”
Section: Discussionmentioning
confidence: 99%